2021
DOI: 10.1038/s41598-021-03326-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of commercial household ultraviolet C germicidal devices in Thailand

Abstract: Ultraviolet C (UVC), or ultraviolet germicidal irradiation (UVGI), is known for its effective air, water, and surface disinfectant properties. With the rise of global awareness about public sanitation and personal hygiene due to the emergence of the current coronavirus disease 2019 pandemic, several applications of UVC were introduced to the commercial market. The present experimental study aimed to evaluate the effectiveness of commercial household UVC germicidal devices for severe acute respiratory syndrome … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In all cases, the effects on air chemistry may still be analogous to those observed in our study, leading to worsened IAQ. Furthermore, UVGI devices developed mainly for household use, where air exchange rates can be very low, also possess potential problems for IAQ. As already discussed in Joo et al (2021) and Collins and Farmer (2021), the impacts of different air and surface cleaning technologies to secondary chemistry need to be acknowledged and should be urgently studied from the perspective of adverse health effects before becoming widely applied in various indoor environments.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the effects on air chemistry may still be analogous to those observed in our study, leading to worsened IAQ. Furthermore, UVGI devices developed mainly for household use, where air exchange rates can be very low, also possess potential problems for IAQ. As already discussed in Joo et al (2021) and Collins and Farmer (2021), the impacts of different air and surface cleaning technologies to secondary chemistry need to be acknowledged and should be urgently studied from the perspective of adverse health effects before becoming widely applied in various indoor environments.…”
Section: Discussionmentioning
confidence: 99%
“…When microorganisms are exposed to UV-C light, some photons are absorbed into the cell membrane, which leads to photo-oxidation and the production of reactive oxygen species (ROS; free radicals) that cause irreversible damage Linden et al, 2019;Palakornkitti et al, 2021). Cellular components such as proteins and nucleotide bases (DNA and RNA) are broken down, preventing cell replication (Chacha et al, 2021;Ravindran & Jaiswal, 2019;Seifert et al, 2016;Singh et al, 2021).…”
Section: Uv-cmentioning
confidence: 99%
“…This leads to a photochemical reaction with dimer formation. The dimers disrupt normal DNA assembly, induce single and double strand breakage, cause mutagenic DNA damage, and affect cellular functions (Hazell et al, 2019;Palakornkitti et al, 2021;Sánchez-Maldonado et al, 2018).…”
Section: Uv-cmentioning
confidence: 99%
“…An evaluation of household UV-C germicidal devices found that several devices are ineffective against SARS-CoV-2, specifically those based on low-dose UV-C light-emitting diodes. However, effective devices based on low-pressure mercury lamps (LMPL) may cause side effects to humans, so that protection for eye and skin while using these devices is suggested ( Palakornkitti et al, 2021 ) [E]. Ozone-free LMPL should be preferred to avoid the generation of significant amounts of ozone, possibly above the legal limit for ozone concentrations in rooms ( Claus, 2021 ) [R].…”
Section: Ultraviolet (Uv) Light [Seda-43 281]mentioning
confidence: 99%